The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17126/joralres.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

Difference in EGFR expression and mean vascular density in normal oral mucosa, oral epithelial dysplasia and oral squamous cell carcinoma.

Abstract: To evaluate the expression of the epidermal growth factor receptor (EGFR) and mean vascular density (MVD) in normal oral mucosa (NOM), oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Material and methods: Descriptive case study. Nineteen histological samples diagnosed with NOM, 18 diagnosed with OED, and 19 with OSCC, were analyzed with immunohistochemistry against EGFR and CD31. EGFR expression was evaluated by extent and intensity of its expression in normal, dysplastic and neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…Fernandez et al (2017) reported the presence of EGFR in normal oral mucosa, indicative of the proliferation of epithelial cells. Receptors were found to be not only limited to basal stratum cells but were also expressed by suprabasal cells [38]. Similar fi ndings regarding the distribution of EGFR immunoreactive epithelial cells were observed in soft tissues of the control group and in CLP aff ected tissues in our patients.…”
Section: Discussionsupporting
confidence: 88%
“…Fernandez et al (2017) reported the presence of EGFR in normal oral mucosa, indicative of the proliferation of epithelial cells. Receptors were found to be not only limited to basal stratum cells but were also expressed by suprabasal cells [38]. Similar fi ndings regarding the distribution of EGFR immunoreactive epithelial cells were observed in soft tissues of the control group and in CLP aff ected tissues in our patients.…”
Section: Discussionsupporting
confidence: 88%
“…With a global incidence of 500,000 per annum, squamous cell carcinoma has been reported to be the most prevalent cancer of the oral cavity [ 1 ]. In South Asia, head and neck cancers are the third leading cause of cancer-related morbidity and mortality [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on CD31 expression revealed no significant difference in the expression of CD31 between fibromas, OEDs, and OSCCs, as well as in normal mucosa, adenoma and adenocarcinoma of colon. It had been proposed that these conflicting results could be attributed to the use of different markers and methods in the micro vessel counting, antigenic retrieval, and inter-observer variations; that all of these factors affect the assessment of MVD 19 . Moreover, the inability of CD31 to distinguish newly formed tumoral blood vessels from normal pre-existing ones in both neoplastic and non-neoplastic tissues 20 .…”
Section: Discussionmentioning
confidence: 99%